The Hyperbole in NCT Dream ISTJ Advertisement Video Using Dyadic Model - Hanifah Ardiani; Andang Saehu; Erlan Aditya Ardiansyah (Jurnal Lingua Idea, 2026)
This research analyzes the hyperbole meaning behind NCT Dream's "ISTJ" album promotional video using Ferdinand de Saussure's dyadic model. The study focuses on identifying the signs embedded in their promotional content and interpreting their associated meanings, like the text which has hyperbole meaning. The qualitative descriptive method were applied by observing promotional video via YouTube. The findings show that the textual elements and symbols convey messages of energy and identity. These are analyzed using Saussure's semiotic framework into signifiers and signifieds, and Claridge’s hyperbole types revealing the meaning of the text. The data collection and analysis process consisted the following five steps based on Basri (2014) and three steps based on Bressler (2007). There are five datums which categorizing into four types of hyperbole found in this analysis from the seven Claridge’s types of hyperbole, that is single-word hyperbole, comparison hyperbole, clausal hyperbole, and the role of superlative. Five of datums being found from the promotional video and the researcher analyzed it, like the text “It feels like a throne”, “Being alone feels like your hands and feet tied up”, “Wait, the sunset is crazy right now”, “I’m too big for one word to capture my personality”, “Simple is the best”. The research contributes to a better understanding of how popular culture and media construct meanings through signs. By using dyadic model theory, this research concludes that NCT Dream's ISTJ album promotional employ signs to construct and communicate layered meanings related to youth, identity, and emotional expression.